Eksperimen Pembelajaran Matematika Melalui Strategi Guided Note Taking Dan Problem Based Learning Ditinjau Dari Motivasi Belajar Siswa Terhadap Hasil Belajar Pada Siswa Kelas Viii Semester 2 MTs Negeri Tinawas - Zulaikhah, Siti; , Drs. H. Ariyanto, M.Pd (2016)
This study aims to describe and analyze: (1) the effect Guided Note Taking and Problem Based Learning in mathematics learning outcomes, (2) effects motitation in mathematics learning outcomes, (3 interaction Guided Note Taking dan Problem Based Learning and motivation in mathematics learning outcomes. The research was conducted students of VIII Grade of MTs Negeri Tinawas of even semester of academic year 2015/2016 with the population all students of VIII a number of 211 students. Type of the research is experiment with quasi experimental design. The class sample of research by using the strastified cluster random sampling. Methods of data collection use documentation and test. Data analyzed by analysis of variance with two different cell lines. The results of data analysis with a significance level of 5% was obtained: (1) there is effect Guided Note Taking dan Problem Based Learning in mathematics learning outcomes, (2) there is effects motivaton in mathematics learning outcomes, (3) there is no interaction Guided Note Taking dan Problem Based Learning in terms motivation in mathematics learning outcomes.